A feminist investigation into the reasons for attrition of women doctors from the South African medical profession and practice : exploring the case of UCT medical school between 1996 and 2005 - Wildschut, Angelique Colleen (Stellenbosch : University of Stellenbosch, 2011)
Thesis (DPhil)--University of Stellenbosch, 2011.